On some classes of submanifolds satisfying Chen's equality in an Euclidean space - Özgür, Cihan; Chand De, Uday (Italian Journal of Pure and Applied Mathematics, 2011)
We study submanifolds satisfying Chen's equality in an Euclidean space. Firstly, we consider projectively semi-symmetric submanifolds satisfying Chen's equality in an Euclidean space. We also study submanifolds satisfying the condition P · P = 0.